MEREMEDIASI MISKONSEPSI SISWA TENTANG PERPINDAHAN KALOR MENGGUNAKAN CLIS BERBANTUAN ANIMASI SWISH MAX - Sismawati, Sismawati; Djudin, Tomo; Arsyid, Syaiful B. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research study aimed to investigate the effectiveness of the Cooperative Learning Integrated with SWiSH Max (CLIS) animation model in remedying misconceptions among seventh-grade students at MTs Muhammadiyah Sejangkung. The research followed a pre "“ experimental design with a one-group pre-test post-test design, and the pattern consisted of 28 students. The instrument used in the study was a multiple-choice test with three options. Before the intervention, the common percent of college students' misconceptions in the pre-test was 72.22%. However, after implementing the CLIS model, the average percentage decreased to 12.85% in the post-test. This indicated a significant improvement in students' understanding, as the percentage of misconceptions reduced to 59.37% after the treatment.The data collected from the pre-test and post-test were analyzed using the Mc Nemar test. The analysis showed that the calculated chi-square value (x2count) of 79.28 was greater than the tabled chi-square value (x2table) of 3.84. This significant result indicated that the use of CLIS with SWiSH Max animation effectively facilitated conceptual changes in the understanding of the heat transfer concept among students. Furthermore, the effectiveness of the remediation was determined to be 0.85, indicating a high level of effectiveness based on the average ratio value. As a result, the CLIS learning model is recommended to teachers as an alternative technique for addressing misconceptions among students when teaching heat transfer concepts